Modelo analítico de la deformación del complejo volcánico chiles-cerro negro observada mediante imágenes interferométricas de radar de apertura sintética (insar) (2020)
Chiles-Cerro Negro volcanic complex (CVCCN) is located on the Colombo-Ecuadorian border and is made up of the Chiles and Cerro Negro stratovolcanoes. By observing Synthetic Aperture Interferometric Radar Images (InSAR) from October 2018 to April 2019 of SENTINEL 1 satellite and its subsequent processing in SNAP (Sentinel Application Platform), a semicircular inflation zone was found between the coordinates 0.70 - 0.75 N and -77.90 - 77.85 E, with values between approximately 2 and 4 cm. Two analytical models were tested to understand the source of this inflation, one with a spherical source (Mogi, 1958) and the other with a spheroidal source (Yang, 1988), of which the spheroidal source was closer to the observed deformation in the interferometric stacking with a volume change of 931.22 ± 5.43 * 10 ^ 4 m ^ 3, a depth of 8000 ± 28.32 m and a maximum deformation of 3.4736 cm.